The Effectiveness of Topical Cefuroxime Powder in Preventing Surgical Site Infection after Elective Paraumbilical Hernia Repair using Polypropylene Mesh - Muhammad Bilal; Mohammad Zarin (Indus Journal of Bioscience Research, 2025)
Background: Paraumbilical hernia repair using polypropylene mesh is a widely accepted surgical approach due to its reduced recurrence rates compared with primary suture repair. However, surgical site infection remains a significant postoperative complication, particularly in patients with comorbidities such as diabetes, obesity, and smoking history. Topical application of cefuroxime powder has been proposed as an adjunctive preventive measure to lower infection risk. Objective: To determine the effectiveness of topical cefuroxime powder in preventing surgical site infection after elective paraumbilical hernia repair using polypropylene mesh as compared to no antibiotic use. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from May 2024 to October 2024 at the Department of General Surgery, Khyber Teaching Hospital, Peshawar. Methodology: A total of 386 patients aged 30–60 years undergoing elective paraumbilical hernia repair with mesh were randomized into two groups of 193 each. Group A received 750 mg topical cefuroxime powder applied over the mesh before closure, while Group B underwent standard repair without topical antibiotic. Postoperative follow-up was performed up to three months. Surgical site infection was diagnosed using Centers for Disease Control and Prevention criteria. Results: Surgical site infection occurred in 6 (3.1%) patients in Group A compared with 20 (10.4%) in Group B (p=0.004). Stratified analysis showed higher infection rates among overweight, diabetic, hypertensive, and smoking patients, with significant reduction in Group A across most subgroups. Conclusion: Topical cefuroxime powder significantly decreases surgical site infections in paraumbilical hernia repair with polypropylene mesh and offers a simple, effective preventive strategy.